Saprotrofní růst a patogenní vlastnosti rodu Lecanicillium (Sordaryomycetes; Clavicipitaceae) - Zdvihalová, Barbora (Jihočeská univerzita, 2014)
Genus Lecanicillium (Sordaryomycetes; Clavicipitaceae) comprises the complex of well-known enthomopathogenic and mycoparasitic fungi. The quality and characteristics of isolates of Lecanicillium spp. can vary on the basis of the origin of fungal isolates and ecological factors. This study compares and evaluates five isolates of Lecanicillium spp. according to its morphological and pathogenic properties.
Saprotrophic growth and pathogenic properties in the genus Lecanicillium (Sordaryomycetes; Clavicipitaceae)